Peningkatan Partisipasi Kunjungan Posyandu melalui Gerakan Posyandu Sehat dan Aktif (GPSAKTI) pada Posyandu Warga Sehati Puskesmas Wonorejo Samarinda - Istiqomah Nur Oktavia; Lia Kurniasari; Nur Jannah (I-Com: Indonesian Community Journal, 2025)
Posyandu (Integrated Health Service Post) is a community-based initiative designed to provide basic health services, particularly for mothers and children. However, low attendance remains a challenge at Posyandu Warga Sehati in Karang Anyar. This community engagement program aimed to increase attendance through the "GPSAKTI" (Healthy and Active Posyandu Movement) initiative. Activities included educational outreach using fan-shaped leaflets, interactive discussions, and training for cadres to create simple sensory educational toys for children. The intervention significantly improved mothers' knowledge about the importance of routine Posyandu visits, with Wilcoxon Signed Rank Test showing a p-value of 0.000. Pre-test scores averaged 58%, while post-test scores increased to 95.33%. Mothers cited barriers such as inconvenient timing and difficult access. The creation of a child-friendly environment with toys increased children's comfort, indirectly supporting regular visits. This initiative demonstrates the importance of health education and community-based collaboration in improving participation in child health programs.